2007
DOI: 10.1167/iovs.06-1014
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Expression Pattern ofPax6in the Pigeon Retina

Abstract: These data suggest that Pax6, a highly conserved gene, can maintain evolutionarily conserved variability at the protein level by alternative splicing and initiation mechanisms, allowing it to perform multiple functions. The variability in the length of the paired domain suggests that the different Pax6 isoforms activate different sets of genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For example, Pax6-5a has a role in inducing embryonic stem cells toward neural differentiation [95]. Each of the two isoforms can regulate its own set of target genes, but they also can have a cumulative effect on the expression of these genes [96,97]. Inami and co-authors (2016) have identified Pах6 transcripts of different classes in C. pyrrhogaster .…”
Section: Transcription Factors and Signal Molecules Characteristicmentioning
confidence: 99%
“…For example, Pax6-5a has a role in inducing embryonic stem cells toward neural differentiation [95]. Each of the two isoforms can regulate its own set of target genes, but they also can have a cumulative effect on the expression of these genes [96,97]. Inami and co-authors (2016) have identified Pах6 transcripts of different classes in C. pyrrhogaster .…”
Section: Transcription Factors and Signal Molecules Characteristicmentioning
confidence: 99%
“…Pax6 is required for development of the pituitary (Estivill-Torrú s et al 2001). Amphioxus Pax4/6 has at least six isoforms, while for vertebrate Pax4 and Pax6 genes 5 and 13 splicing events, respectively, have been identified (Bandah et al 2007;Short and Holland 2008). Only two of four isoforms of Pax4 identified in the mouse are expressed in the developing pituitary (Rath et al 2009), indicative of the roles that differential expression of isoforms play in development.…”
Section: Alternatively Spliced Isoforms Are Differentially Expressed mentioning
confidence: 99%
“…The PAX6 gene is part of the well-studied paired box gene family (PAX), which encodes transcription factors for many developmental processes and is subject to heavy alternative splicing [24-26]--41 transcripts were found in a gene in the pigeon retina [27]. The canonical isoform is characterized by an N-terminal paired domain followed by a linker, a paired-type homeodomain, and a (P/S/T)-rich C-terminal domain, yielding a 422-amino-acid protein (437 in zebrafish).…”
Section: Resultsmentioning
confidence: 99%